The sGC stimulator riociguat inhibits platelet function in washed platelets but not in whole blood. (18th October 2015) - Reiss, C.; Mindukshev, I.; Bischoff, V.; Subramanian, H.; Kehrer, L.; Friebe, A.; Stasch, J.‐P.; Gambaryan, S.; Walter, U.
Abstract : Background and Purpose: Stimulation of soluble guanylyl cyclase (sGC) is a valuable therapeutic strategy for the treatment of several cardiovascular diseases. The sGC stimulator riociguat has been approved for the treatment of two forms of pulmonary hypertension. Platelets contain large amounts of sGC and play a key role in the regulation of haemostasis. Therefore, we investigated the effects of riociguat on platelet function. Experimental Approach: The effect of riociguat treatment on human platelet activation and aggregation was investigated. The sGC‐specific effects of riociguat were determined by comparing wild‐type and platelet‐specific sGC‐knockout mice. Key Results: Riociguat induced cGMP synthesis and subsequent PKG activation in human platelets, suggesting that the inhibitory effects are mediated by cGMP signalling. This finding was confirmed when sGC‐knockout platelets were not inhibited by riociguat. In washed human platelets, 100 nM riociguat reduced ADP‐induced GPIIb/IIIa activation, while a 10‐fold higher concentration was required to reduce convulxin‐stimulated GPIIb/IIIa activation. Riociguat inhibited ADP‐induced platelet shape change and aggregation, while ATP‐induced shape change remained unaffected. However, in PRP and whole blood, 50–100 μM riociguat was required to inhibit platelet activation and aggregation. Riociguat in combination with iloprost significantly inhibited platelet aggregation, even in whole blood. Conclusions and Implications: Riociguat inhibits platelet activation in whole blood only at concentrations above 50 μM, while the plasma concentrations in riociguat‐treated patients are 150 to 500 nM. This finding indicates that riociguat treatment does not affect platelet function in patients. Nevertheless, the possibility that riociguat acts synergistically with iloprost to inhibit platelet activation should be considered.